The potency of obestatin in improving kidney functions and apoptosis in rats with cisplatin-induced acute kidney injury - ÖZDEMİR KUMRAL, ZARİFE NİGAR; BULUT, ALİSİNA; ÖZKAN YENAL, NAZİYE; YEGEN, BERRAK; KOÇ, MEHMET (My University, 2022)
© 2022 Marmara University Press.Cisplatin (CP), which is the most commonly used anticancer agent to treat several solid tumors, may cause acute kidney injury (AKI) as the major limiting factor for its clinical use. Obestatin (OB) is a ghrelin gene-derived peptide produced in several tissues and has shown anti-oxidant, anti-apoptotic, and anti-inflammatory effects in many experimental models. This study investigated the effect of OB treatment on nephrotoxicity induced by CP. Rats were divided into 4 groups as two control (1 ml/kg, saline, intraperitoneal (ip), single dose) and two CP-induced (7 mg/kg, ip, single dose) AKI groups (8 rats in each group). Immediately after the CP injection and the following two days, injections of OB (10 µg/kg, ip) were performed. Rats were decapitated at the end of 72 hours. Blood and kidney tissue samples were taken for biochemical and histopathological measurements. The results of the present study revealed that serum creatinine and BUN levels were significantly increased in the CP-induced AKI group when compared to the control group. Treatment with OB improved kidney functions and ameliorated renal oxidative injury and maintained oxidative balance in the CP-induced AKI model, which was revealed by elevated malondialdehyde and depleted glutathione levels. TUNEL scores also demonstrated that CP increased the apoptotic response, while OB treatment abolished it. CP-induced medullary and cortical injuries were also partially reversed by OB treatment. Thus, our findings show that OB alleviates CP-induced nephrotoxicity in rats through the abolishment of oxidative stress and apoptosis.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); acute kidney injury; apoptosis; cisplatin; obestatin; rat